HELIUM, NEON, AND ARGON ABUNDANCES IN THE SOLAR WIND: IN VACUO ETCHING OF METEORITIC IRON-NICKEL - Murer C.A.; Baur H.; Signer P.; Wieler R. (My University, 1997)
Helium, neon, and argon in metallic Fe-Ni separated from the three solar-gas-rich H-chondritic meteorites Acfer111, Fayetteville, and Noblesville were analysed by stepped etching in vacuo. The isotopic composition of the gases, particularly of neon, varies in the course of the etching in a very similar way as previously observed for lunar and meteoritic plagioclase, pyroxene, and ilmenite. This shows that also meteoritic metal contains an isotopically light solar-wind component (SW) near grain surfaces and a heavier solar energetic particle component (SEP) at larger depths. On the other hand, elemental ratio profiles He/Ar and Ne/Ar in Fe-Ni form a striking contrast to these profiles in silicate and oxide minerals. In the latter, He and Ne are clearly depleted in the outer layers, indicating a loss of light SW noble gases, but no such elemental fractionation is observed for Fe-Ni, with the probable exception of a depletion of He in Noblesville. This allows us to deduce the relative abundances of He, Ne, and Ar in the solar corpuscular radiation trapped in the meteoritic parent regoliths. The values for all three meteorites agree with each other. The mean ratios 4He/36Ar = 30400 +/- 2200 and 20Ne/36Ar = 47 +/- 3 for SW + SEP are close to those determined for present-day SW by the Apollo solar wind composition experiment. In particular, the 36Ar abundance obtained in the latter experiment after correcting for an excess component is very similar to the value deduced here. The concentration ratio SEP-Ne/SW-Ne in Fe-Ni is similarly high (30-50%) as in plagioclase, pyroxene, and ilmenite. The high SEP-Ne concentration in Fe-Ni requires a high flux of solar particles with energies less than about 0.1 MeV/amu.